Maximal Subgroups of the Group PSL(11, 2) - Elkhatib, Rauhie I. (Thamar University Journal of Natural & Applied Sciences, 2023)
In this note, we will determine, up to the conjugacy, all the maximal subgroups of PSL(11, 2) by Aschbacher’s theorem.